2004
DOI: 10.1124/jpet.104.076042
|View full text |Cite
|
Sign up to set email alerts
|

Cellular G Protein-Coupled Receptor Kinase Levels Regulate Sensitivity of the α2B-Adrenergic Receptor to Undergo Agonist-Induced Down-Regulation

Abstract: Chronic coactivation of ␣ 2B -and ␤ 2 -adrenoceptors (AR) was recently reported to down-regulate the ␣ 2B -AR at a lower threshold epinephrine (EPI) concentration compared with the activation of ␣ 2B -AR alone. This is the result of a modest ␤ 2 -AR-dependent up-regulation of G protein-coupled receptor kinase 3 (GRK3). In the present study, we determined that increasing GRK2 or GRK3 levels, independent of ␤ 2 -AR activation, decreases the EC 50 concentration for agonist-induced down-regulation of the ␣ 2B -AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The human ␣ 2A -AR mutant (Del 293-304) that lacks the four serine residues in the third intracellular loop thought to be phosphorylated by GRKs does not acutely desensitize but does undergo down-regulation (Jewell-Motz et al, 1997). In contrast to these observations, recent studies in BE(2)-C and BN17 cells and in GRK3-and GRK2-overexpressing NG108 cells suggest that the ␣ 2A -and ␣ 2B -AR are rendered more sensitive to agonist-induced down-regulation because of a 2-to 3-fold up-regulation of GRK3 (Bawa et al, 2003;Desai et al, 2004Desai et al, , 2005. In addition, mutation of potential GRK phosphorylation sites ( 322 SSTS 325 changed to AAVA) in the third intracellular loop of opossum ␣ 2C -AR prevents receptor down-regulation after 24-h exposure to 0.3 M NE (Deupree et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The human ␣ 2A -AR mutant (Del 293-304) that lacks the four serine residues in the third intracellular loop thought to be phosphorylated by GRKs does not acutely desensitize but does undergo down-regulation (Jewell-Motz et al, 1997). In contrast to these observations, recent studies in BE(2)-C and BN17 cells and in GRK3-and GRK2-overexpressing NG108 cells suggest that the ␣ 2A -and ␣ 2B -AR are rendered more sensitive to agonist-induced down-regulation because of a 2-to 3-fold up-regulation of GRK3 (Bawa et al, 2003;Desai et al, 2004Desai et al, , 2005. In addition, mutation of potential GRK phosphorylation sites ( 322 SSTS 325 changed to AAVA) in the third intracellular loop of opossum ␣ 2C -AR prevents receptor down-regulation after 24-h exposure to 0.3 M NE (Deupree et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
“…One explanation for these conflicting reports could be the difference in level of receptor expression between the different studies. In studies supporting the role of GRKs in down-regulation, the receptor was expressed at levels Յ300 fmol/mg protein (Deupree et al, 2002;Desai et al, 2004Desai et al, , 2005, whereas the negative results were observed in systems in which receptor expression was Ն700 fmol/mg protein (Eason et al, 1994;Jewell-Motz and Liggett, 1995;Jewell-Motz et al, 1997). Another contributing factor could be the low levels of expression of GRKs in CHO and COS cells commonly used for these studies (Menard et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations